Technical variations of diverticular jejunal loops - Baldizán, Jorge; González, Jorge; Armand Ugón, Alfredo; Perdomo, M´áximo; Juambeltz, Carlos (Cirugía del Uruguay, 1986)
Analysis of the difieren! forms of diverticular ansas starting from Braun's (1892) and Roux's (1896) procedures and as modified by Valdoni's, Hivet-Warren's and Praderi's innovations. The las! one is used in biliary and gastric surgery alter total removal of the stomach or for the conversion Billroth 11 with alkaline gastritis. Finally, study of applications proposed by Pereyra Lim3 and Defelitto.